Eksistensi CV. Andromeda Utama untuk Menghadapi Persaingan Usaha dalam Perspektif Manajemen Pemasaran Syari’ah - Abdul Hamid (Iqtishodiyah : Jurnal Ekonomi dan Bisnis Islam, 2019)
In the world of entrepreneurship, competition is a matter of course. Competition is the color of entrepreneurship. Without competition, the work feels bland. Competition is also a motivation to advance business and make the workforce more enthusiastic about facing obstacles. Competition can also have a negative impact on our business world if an entrepreneur is unable to control himself in the face of competition so that entrepreneurs compete imperfectly or unhealthily. This is also fatal for a company. The existence of CV. Andromeda Utama in facing business competition, especially in the field of tourism, deserves more attention, this is because CV. Andromeda Utama is classified as a new company and is an individual business compared to other tourism service companies that are much longer in this field and are a company managed by several people who are experienced and more experts in this field.